Pengaruh Aplikasi Limbah Cair Pabrik Kelapa Sawit terhadap Hasil Kedelai dan Perubahan Sifat Kimia Tanah Ultisol - Ermadani , (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
The aim of this research was to evaluate the effect of palm oil mill effl uent (POME) and its residue on yield of soybean (Glycine max L.) and soil chemical properties. Field experiment was done on Ultisol soil in Brasau Village, Tungkal Ulu, Tanjung Jabung Barat District from March to November 2009. In the experiment, soybean was planted twice. At fi rst planting, the treatments were without POME as control with application of 50 kg urea ha-1, 150 kg SP-36 ha-1, 100 kg KCl ha-1, 5 ton manure ha-1 and 2 ton dolomite ha-1, and POME application consisting of 50,000 L ha-1, 100,000 L ha-1, 150,000 L ha-1 , 50,000 L ha-1 + 150 kg SP-36 ha-1, 100,000 L ha-1 + 150 kg SP-36 ha-1, 150,000 L ha-1 + 150 kg SP-36 ha-1. Treatments were replicated four times and arranged in a randomized block design. At second planting, plots were treated with half of fi rst planting doses of POME. The results showed that the content of N, P, and K of plant tissue and dry weight of soybean seed were increased with increasing dose of POME. The highest yield of soybean at fi rst planting was 2.15 ton ha-1, and achieved with the application of 150,000 L POME ha-1 + 150 kg SP-36 ha-1 , while at second planting the highest dry weight of soybean seed was 2.01 ton ha-1 by residue of 150,000 L POME ha-1 and 150 kg SP-36 ha-1+ application of 75,000 L POME ha-1. Moreover, improvement of soil chemical properties were showed by increasing organic C, cation exchange capacity, total N, total P, available P, and exchangeable K and decreasing exchangeable Al. Keywords: POME, residue, Ultisol, Glycine max (L)